Study on Factors Influencing the Utilization Level of Combine Harvester by Farmers - Rangga, Kordiyana K.; Efendi, Irwan; Listiana, Indah; Utami, Tataning (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The aim of this research is to determine the level of use of combine harvesters and the factors that influence it. The research location was chosen deliberately, namely in Negeri Katon District which received assistance from 3 combine harvester units. The respondents in this study were 53 farmers from 3 farmer groups who received combine harvester assistance. The data collected was analyzed using descriptive analysis and the Kendall tau statistical test. The results of the research show that the level of use of combine harvesters on the indicators of plant condition requirements shows a good category, where farmers harvest rice when it reaches the optimum age. The indicator for plant condition requirements shows a fairly good category, where farmers harvest when the land is dry, but farmers never confirm whether the land conditions are dangerous and can damage machinery. The machine application indicator shows the poor category, where the intensity of farmers using combine harvester machines is 3 - 4 times in 5 harvest seasons, and farmers are still less skilled in operating combine harvesters. Factors related to the use of combine harvesters by farmers are land area, relative profit, compatibility, complexity, trialability, observability, and the role of farm extension workers. Keywords: Compatibility, Complexity, extension workers, Observability, Relative profit.